Integrative crosstalk between hypoxia and the cold: Old data and new opportunities - Mugele, Hendrik; Oliver, Samuel J.; Gagnon, Daniel; Lawley, Justin S. (Experimental physiology, 2021)
New Findings What is the topic of this review? The aim was to examine the influence of hypoxia on thermoregulatory and cardiovascular control in the cold. What advances does it highlight? Exposure to hypoxia seems to alter both thermoregulatory and cardiovascular control, but these conclusions are based on limited data, and this review highlights the need for future research in this area. Cold stress and hypoxia have been the subject of research for decades; however, humans often encounter these stressors together, such as in the alpine environment. Therefore, this review summarizes previous data with respect to the influence of hypoxia on thermoregulatory and cardiovascular control in the cold and presents new ideas for the future. Altogether, little to no evidence is available on the integrative and adaptive mechanisms by which the human body regulates heat conservation, oxygen delivery and maintenance of blood pressure.